2018
DOI: 10.1038/s41419-018-0713-8
|View full text |Cite
|
Sign up to set email alerts
|

Placental exosome-mediated Bta-miR-499-Lin28B/let-7 axis regulates inflammatory bias during early pregnancy

Abstract: Abnormal inflammatory bias in the maternal-fetal interface leads to reproductive failure in mammals. Placental exosomes are involved in maternal-fetal communication during pregnancy. However, whether the placenta or fetus is involved in regulating the balance of uterine local inflammation through exosomes remains unclear, and the mechanism must be further explored. Here we demonstrated that placenta-specific exosomes are abundant in the peripheral blood of dairy cows during early pregnancy and selectively load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…In these miRNAs, sssc-let-7a, ssc-let-7d-5p, ssc-let-7e, ssc-let-7f-5p, ssc-let-7g, ssc-let-7i-5p, ssc-miR-181c and ssc-miR-451 were cluster into Profile 6, while ssc-miR-21-5p, ssc-26a-5p and ssc-miR-181a were cluster into Profile5. A recent study demonstrated that let-7 family involved in the Lin28B/let-7 axis, which is the key regulatory mechanism of the immune inflammatory response during early pregnancy in cattle and the angiogenesis during the development of human malignances [49,50]. In addition, ssc-miR-181a and ssc-miR-181c may regulate embryo implantation by targeting SPP1 (adhesion molecule) in porcine endometrium [51].…”
Section: De Mirnas Related To Proliferation Immunization and Angiogementioning
confidence: 99%
“…In these miRNAs, sssc-let-7a, ssc-let-7d-5p, ssc-let-7e, ssc-let-7f-5p, ssc-let-7g, ssc-let-7i-5p, ssc-miR-181c and ssc-miR-451 were cluster into Profile 6, while ssc-miR-21-5p, ssc-26a-5p and ssc-miR-181a were cluster into Profile5. A recent study demonstrated that let-7 family involved in the Lin28B/let-7 axis, which is the key regulatory mechanism of the immune inflammatory response during early pregnancy in cattle and the angiogenesis during the development of human malignances [49,50]. In addition, ssc-miR-181a and ssc-miR-181c may regulate embryo implantation by targeting SPP1 (adhesion molecule) in porcine endometrium [51].…”
Section: De Mirnas Related To Proliferation Immunization and Angiogementioning
confidence: 99%
“…Moreover, let-7a, let-7c, let-7g and let-7i are involved the Lin28B/let-7 axis, which is the key regulatory mechanism of the immune inflammatory response during early pregnancy in cattle [35].…”
Section: Discussionmentioning
confidence: 99%
“…In cattle, placenta-derived exosomes are abundant in the circulation of pregnant cows and exosome-derived miR-499 attenuated the expression of proinflammatory cytokines by inhibiting NF-κB signaling, thereby attenuating inflammatory responses and forming an immune-tolerant microenvironment in the uterus. Inhibition of miR-499 lead to inflammatory deregulation and increased risk of pregnancy failure [56].…”
Section: The Influence Of Pregnancy-associated Evs On the Maternal Immentioning
confidence: 99%